QUANTIFICATION OF PREDICTABLE CLINICAL-BIOLOGICAL INDICES FOR A CORRECT PROIMPLANTATION DIAGNOSIS - Agop-Forna Doriana; Oana Cucoveica; Mihaela Viziru; Tibeica Andreea; Cretu Cosmin; Curca Razvan; Norina Forna (Romanian Dental Association for Education, 2023)
Aim of the study The success of the implant therapy is co-dependent on the correct pre-implant assessment of the general, loco-regional and local status, the surgical and post-surgical stage or prosthetics as well as maintenance. In order to appreciate and evaluate the candidate for implanted therapy, a series of markers or clinical-biological indices are followed. The present paper proposes an updated synthesis of the opinions from the specialized literature regarding them, with the aim of preparing an update regarding the scientific results of recent years. Material and methods Systematic reviews, meta-analyses on the influence of general and local factors on the success of implant therapy, clinical-biological indices, success rate, peri-implantation, using electronic platforms available until June 26, 2023, were included for analysis. ​Results Clinical-biological indicators of general condition influence the patient's response both in the immediate post-therapeutic healing stage and long-term implant retention. At the same time, the patient's general condition conditions the time and extent of the surgical intervention. Conclusions A number of general conditions are mentioned in the literature that contraindicate the surgical intervention in ambulatory conditions, such as myocardial infarction more recent than 6-12 months, acute leukemia, stroke more recent than 12 months.